2019
DOI: 10.1115/1.4044496
|View full text |Cite
|
Sign up to set email alerts
|

On the Effects of Tip Clearance and Operating Condition on the Flow Structures Within an Axial Turbomachine Rotor Passage

Abstract: Effects of tip clearance size and flowrate on the flow around the tip of an axial turbomachine rotor are studied experimentally. Visualizations and stereo-particle image velocimetry (PIV) measurements in a refractive index-matched facility compare the performance, leakage velocity, and the trajectory, growth rate, and strength of the tip leakage vortex (TLV) for gaps of 0.49% and 2.3% of the blade chord, and two flowrates. Enlarging the tip clearance delays the TLV breakup in the aft part of the rotor passage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Li et al [5] experimentally investigated the effect of tip clearance size and flow rate on the flow rate around the tip of an axial turbomachine rotor and found that the generation position and movement trajectory of the clearance vortex system change depending on the clearance width, which in turn affects the clearance turbulence losses. Through numerical simulation, Wu et al [6] found that the C-shaped groove can effectively reduce the flow rate of tip leakage flow, thereby inhibiting the generation of high-speed leakage flow.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [5] experimentally investigated the effect of tip clearance size and flow rate on the flow rate around the tip of an axial turbomachine rotor and found that the generation position and movement trajectory of the clearance vortex system change depending on the clearance width, which in turn affects the clearance turbulence losses. Through numerical simulation, Wu et al [6] found that the C-shaped groove can effectively reduce the flow rate of tip leakage flow, thereby inhibiting the generation of high-speed leakage flow.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the most advanced research on the Tip Leakage Vortex (TLV) phenomenon is in the field of compressors. In recent years, researchers have analyzed experimental data from axial compressors [24][25][26], employing a cavity model with longitudinal slots to simulate the interaction between the TLF mainstream and jet, as well as the rolling up of TLV [27], simplifying the complex internal flow path of the impeller. Direct numerical simulation (DNS) studies on the leakage model of rotors [28] have shown that simple model flows, when simulated with high precision, can adequately depict the development and evolution of leakage vortices.…”
Section: Introductionmentioning
confidence: 99%